Distribution, source, and ecological risk assessment of PAHs among size and density fractions in contaminated sediments from the Yellow River of Henan section. Issue 2 (3rd April 2019) - Xi, Nannan; Guo, Wei; Feng, Jinglan; Liu, Shuhui; Sun, Jianhui
Abstract: This study investigated particle size and density distributions of polycyclic aromatic hydrocarbons (PAHs) in two surface sediments (JZ and KF), collected from the Yellow River of Henan section, China. The concentrations of Σ15 PAHs ranged from 35.6 to 45862 ng g −1 dry wt, which were greatly elevated in coarse particles and low-density fractions. The Σ15 PAHs concentrations in low-density fractions were 533 (JZ) and 996 (KF) times higher than those in the corresponding high-density fractions. However, due to relatively less quantities of low-density fractions (0.27–2.33%), most of the PAHs were contributed by the high-density components. For both sediments, the influence factors of PAHs source in the environment were very complex, more so than the level of TOC and BC content. JZ sediment was dominated by 4-ring to 6-ring PAHs (61.5–75.1%), while, 2-ring to 3-ring PAHs were abundant in KF samples (39.8–72.6%). Ratios of specific PAHs reflected PAHs among the size- and density-fraction of each sediment may be contaminated by mixed of pyrolytic and petrogenic origin. Additionally, ecological risk assessment of PAHs suggested that total toxic equivalent values of PAHs in the low-density fractions were much higher than those of the corresponding high-density fractions in the studied area.